Analisis Perbandingan Harga Saham PT Garuda Indonesia Persero (Tbk.) Sebelum dan Sesudah Pandemi Covid-19 - Joanne V. Mangindaan; Hendrik Manossoh (Universitas Sam Ratulangi, 2020)
The COVID-19 pandemic is one emergency event that has shaken the stock market around the world. Share prices of companies in various parts of the world have experienced an unprecedented decline. This study attempts to analyse the impact of the COVID-19 pandemic on PT Garuda Indonesia (Persero) Tbk by comparing the mean of share price of the company prior and post the announcement of first confirmed case of COVID-19 in Indonesia. The first confirmed case of COVID-19 in Indonesia was announced on 2 March 2020. The result of this study shows that there was a significant decline in the company’s share price during the 30-day period after the announcement in compared to the share price in the 30-day period before the announcement.